Analisis Strategi Manajemen Pemasaran Dalam Meningkatkan Penjualan pada Toko Syurga Kurma Kecamatan Medan Tembung - Arinah Syahira; Rinda Arista; Yungki Akbar (MES Management Journal, 2023)
With the development of technology and economic growth, especially in the business world, with the emergence of various businesses/souvenir businesses that try to provide a variety of attractive services and products to meet the needs and interest of consumers. The occurrence of various changes in the business/business world is a common thing to happen because marketing will be faced with various changing conditions, so that business people must move according to market changes, namely by changing marketing management according to changing situations and conditions of consumers. This study aims to find out how marketing management is implemented by the Surya Dates shop and whether the management strategy implemented is effective in increasing sales and to find out the obstacles that are felt when carrying out the implementation of this management strategy. The research method used in this study is a qualitative research method with a descriptive research approach where the data in the research were obtained by interview, observation and literature review to find out how the management strategy was implemented by the Surya Dates store. Keywords: Management Strategy, Marketing, Sales Increase